Sha'rawi's Perception of Economic Solutions for Home Women in QS Al-Ahzab Verse 33 with Tahlili Approach - Annisa Az Zahra; Yeti Dahliana; Andri Nirwana AN (al-Afkar, Journal For Islamic Studies, 2024)
The debate between women being allowed to leave the house or stay at home has a long discussion. There are two opposing views on this matter. Looking at the problems discussed, the author uses the tahlili approach method which focuses on the words "وَقَرْنَ فِيْ بُيُوْتِكُنَّ " (let you (women) remain in your house), which takes the view that according to Sheikh Muhammad Mutawalli Al-Sha'rawi, he is of the view that women are not allowed to work outside the home because of the many effects of slander that will occur if women do a lot of activities outside the home. In the end, it can be concluded that in the explanation of his interpretation, Sha'rawi provides alternative solutions so that women can work to meet their needs or help their household needs by making creativity or handicrafts that can be done from home and can later be sold. When juxtaposed in today's modern era, women can use social media and sell their services through social media or online, this avoids women working outside the home in order to remain responsible for their domestic work.